FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STUNTING PADA BALITA USIA 24-59 BULAN DI WILAYAH KERJA PUSKESMAS RAWAT INAP GEDONG TATAAN KAB. PESAWARAN TAHUN 2021 - Fitriani, Yulies; Nurhartanto, Adhi (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Stunting is still a nutritional problem during the growth and development of children in Indonesia, which describes chronic undernutrition status during growth and development since early life. The nutritional status prevalence of stunting for under-five-year-old children in Pesawaran district in 2018 was 27.49%. Sixty eight children under five was discovered in Inpatient Health Center of Gedong Tataan subdistrict. This study aims to determine the factors that influence stunting in toddlers aged 24-59 months in the working area of ​​the Gedong Tataan Inpatient Health Center. This is an observational study with a case control design using secondary data from the mother's KIA (Mother and Child Health) book and primary data through interviews. The observed variables were child’s gender, history of pregnant women with KEK (Chronic Energy Deficiency/SEZ), history of Low Birth Wight (LBW), history of exclusive breastfeeding, mother's education, parents' occupation, immunization status and environmental sanitation. The sampling technique used in this study is simple random sampling. The numbers of samples in this study were 78 samples which included 39 case groups and 39 control groups. From the bivariate, it is obtained that variables which affect stunting are history of low birth weight p-value 0,012 OR 2,219 (1,716-2,868), history of exclusive breastfeeding p-value 0,001OR 6,2000 (2,258-17,024), environmental sanitation p-value 0,008 OR 8,222 (1,699-39,799). From the results, it is recommended for GedongTataan Inpatient Health Center officers to increase the provision of education to the community, especially to woman of childbearing age (WUS) and pregnant women about nutrition in the First 1000 Days of Life (HPK) and Clean and Healthy Life Behavior (PHBS).